Nutrition Education Using E-Booklet Against Hemoglobin Levels of Young Women - Podojoyo, Podojoyo; Syafira, Adillah; Hartati, Yuli; Kusumawaty, Ira (International Journal of Public Health Excellence (IJPHE), 2023)
Anemia in adolescent girls is characterized by Hb levels < 12 g / dl. Anemia is influenced by various factors including nutritional intake, and knowledge. Anemia results in learning concentration, fatigue, to decreased learning achievement. One of them overcomes this problem by giving Fe supplements and nutrition education. The purpose of this study was to determine the relationship between nutrition education using e-booklets on hemoglobin levels in adolescent girls. The design of this study was a Quasi-Experiment with a comparison group. The study was divided into the treatment group and the comparison group. Providing nutrition education using e-booklets and Fe supplements for 3 weeks in the treatment group. The number of respondents was 36 in the treatment group and the comparison in the comparison group. The results of the t-dependent test showed an average difference in the two groups with a p-value of  0.05. The average hemoglobin level of the treatment group was 0.411 g / dl and the comparison group was 0.2 g / dl. The results of the t-independent test showed no difference in the average hemoglobin levels of the treatment group with a comparison group with a p-value of  0.05. The average difference in hemoglobin levels in the treatment group with the comparison group was 0.211 g / dl. Fe supplements and nutrition education with e-booklets can increase Hb levels.